Methods for Detecting Early Symptoms of Stroke: A Literature Review - Bambang Suryadi (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: In the world every 2 seconds 1 person suffers from a stroke, and 16% of the world's population experiences a stroke in their lifetime, every 4 seconds 1 person dies. The initial symptoms of a stroke must be recognized quickly until the stroke patient's golden period of 4.5 hours is over so that there is no wider damage to brain tissue due to a lack of oxygen for too long which causes brain cells (neurons) to die and connections or connections between neurons (synapses) to be lost. can cause paralysis, blurred vision, difficulty speaking, decreased consciousness and even death. Objectives: To analyze the Early Symptom Detection Method of Stroke. Methods: The authors conducted a PRISMA-style systematic review of Stroke Early Symptom Detection Methods in various countries. Using five articles that were used and then included for analysis and interpretation. Results: There are two methods for early detection of early symptoms of stroke that can be used to detect early symptoms of stroke, namely F.A.S.T and BE-FAST. Both methods have the same accuracy and have an optimal limit for detecting stroke of ≥1. Conclusion: There are two methods for early detection of early symptoms of stroke that can be used to detect early symptoms of stroke, namely F.A.S.T and BE-FAST, for this reason these methods need to be disseminated to the public. So it has the impact of being able to increase knowledge about stroke symptom detection which can increase timely stroke detection before the golden period ends.